Avaliação de técnicas de soldagem MIG/MAG para deposição com arames AWS ERNiCrMo-3 e ER80S-B2 em aço estrutural ASTM A387 Gr.11 - Cavalcante, Nathália Escóssio (2016)
The ASTM A387 Gr.11 steel is widely used in the oil & gas industry in applications at elevated pressures and temperatures, such as “coke drums”. Due to the work regime, coke drums undergo continuous variation in temperature along its length and thus, the thermal gradients and pressure variations for each operating cycle occurs. As a result, many problems can arise as hydrogen embrittlement and the appearance of "bulges". The bulges are preferred sites for cracking nucleation in coke drums. The actions commonly taken to solve the problems associated to cracking are the repair of cracked area by welding techniques. However, the application of many of these techniques, found operational and metallurgical problems that compromises the performance of welded components. Thus, this work aims to development and evaluation of repair techniques by welding, using the double layer temper bead technique in components made of ASTM A387 Gr.11 steel providing good mechanical and microstructural properties. The methodology of this study was divided into many stages, among them the application of hardness and microstructure evaluation criteria for determining the best welding conditions followed by the welding and characterization of the coatings. The influence of the control factors, such as welding heat input and waving was evaluated. Two filler metals were used: AWS ERNiCrMo-3 Ni based alloy (similar to alloy Inconel 625) and AWS ER80S-B2 low carbon steel (similar to the ASTM A387 Gr.11 steel) and three gas mixtures (Ar + 25% He, Ar + 4 % CO2 and Ar + 38%He + 4%CO2). The waving and welding heat input had influence on geometric features of the weld beads. The microstructure found in the heat affected zone of coatings consisted of bainite and tempered martensite. In the five welding conditions identified by the decision diagram it was found a significant grain refinement and a reduction in hardness values, when compared to the same conditions welded with single deposition proving the effectiveness of the double layer temper bead technique. In three of these conditions, the maximum hardness in the HAZ of the coatings was less than 237 HV, as required by the welding standard N-133 from Petrobras